Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek
Wydawnictwo:Nowa Era
Rok wydania:2015
Rozwiąż równanie 4.86 gwiazdek na podstawie 7 opinii

`a)\ x^12/x^9=64`  

`\ \ \ x^(12-9)=64` 

`\ \ \ x^3=64` 

`\ \ \ x=root(3)64=4` 

 

 

 

`b)\ x^7/x^-3=1024` 

`\ \ \ x^(7-(-3))=1024` 

`\ \ \ x^(7+3)=1024` 

`\ \ \ x^10=1024` 

`\ \ \ x=root(10)1024=2` 

 

 

 

`c)\ (x^5*x^4)/(x^2)^3=27` 

`\ \ \ (x^(5+4))/(x^(2*3))=27` 

`\ \ \ x^9/x^6=27` 

`\ \ \ x^(9-6)=27` 

`\ \ \ x^3=27` 

`\ \ \ x=root(3)27=3` 

 

 

 

`d)\ (x^7*x^-3)/(x^-1)=32` 

`\ \ \ (x^(7+(-3)))/(x^-1)=32`  

`\ \ \ x^4/x^-1=32` 

`\ \ \ x^(4-(-1))=32` 

`\ \ \ x^(4+1)=32` 

`\ \ \ x^5=32` 

`\ \ \ x=root(5)32=2` 

 

 

 

`e)\ ((x^2)^-3*x)/((x^-2)^2)=2/7`  

`\ \ \ (x^-6*x)/(x^-4)=2/7` 

`\ \ \ x^-5/x^-4=2/7` 

`\ \ \ x^(-5-(-4))=2/7` 

`\ \ \ x^(-5+4)=2/7` 

`\ \ \ x^-1=2/7` 

`\ \ \ x=(2/7)^-1=7/2=3 1/2` 

 

 

`f)\ (x^-4*x^-7)/((x^2)^-4)=1/8` 

`\ \ \ (x^-11)/(x^-8)=1/8` 

`\ \ \ x^(-11-(-8))=1/8` 

`\ \ \ x^(-11+8)=1/8` 

`\ \ \ x^-3=1/8` 

`\ \ \ x^3=(1/8)^-1` 

`\ \ \ x^3=8` 

`\ \ \ x=root(3)8=2`